Doing the single person study in human computer interaction (HCI) / Fariza Hanis Abdul Razak and Alan Dix - Abdul Razak, Fariza Hanis; Alan, Dix (Faculty of Computer and Mathematical Sciences, 2010)
This paper presents how a single person study can be done in the field of Human Computer Interaction (HCI). This single person study was explored using a participant observation method known as Friendship Observation that utilises more personal data gathering tools such as diary studies, text messages and personal emails. Since interpretation of the data was done based on the research-subject relationship, some ethical issues related to the reliability, and validity of the data were raised. Despite this criticism, this type of study can offer some potential benefits to HCI community such as a methodology for a user-centred design and designing affective interaction.